Pengaruh Penerapan Model Pembelajaran Klasikal pada Asfek Perkembangan Anak Usia Dini di TK Al Falah - Eni Nuraeni; Ema Hanapiah; Novi Yanti Ulpah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Children aged 0 to 5 years is a golden age (golden age). This period is an ideal time for children to seek, learn and acquire basic concepts that affect children's lives in the future. The implementation ofthe classical learning model applied in PAUD institutions has notfully referred to the 2013 curriculum menu. Then where PAUD teaching staffis still minimal, there are junior and senior high school graduates or undergraduates who have not graduated so that in practice it does not run optimally. This study aims to describe how the implementation of the classical learning model in Al Falah Kindergarten, Langkaplanca District. The method in this research is observation and interview. The data obtained are primary data. The results of the observations show that the implementation of the application of the classical learning model is of